Tobacco Products, Periodontal Health and Education Level: Cohort Study from Sweden - Anna Julkunen-Iivari; Anna Maria Heikkinen; Ismo T. Räisänen; Hellevi Ruokonen; Jukka H. Meurman; Sanna Toppila-Salmi; Per-Östen Söder; Birgitta Söder (MDPI AG, 2020)
Background: The aim of this study is to investigate if using tobacco products (including snuff, smoking tobacco and dual-using) associates with periodontal health, education level and mortality in a Swedish cohort, hypothesizing that tobacco products affect periodontal health, associate with lower education and increase the risk of death. Method: Study cohort of 1080 subjects aged 31-40 years (528 men, 552 women) was clinically examined and interviewed in 1985 and followed for mortality until 2015. Subjects were classified into two groups: "tobacco users" and "non-users". Associations between periodontal health parameters, tobacco products, education level and age of death were analysed. SPSS was used for analyses. Results: Tobacco products, as well as education level associated, with poor periodontal health. Tobacco users and lower education was linked to higher plaque-, calculus- and gingival-index scores than non-users (p < 0.001). They also had significantly higher prevalence of deep periodontal pockets (≥5 mm) (p < 0.001 and 0.010, respectively), missing teeth (p = 0.010 and 0.003, respectively) and lower education level (p < 0.001) compared with non-users. However, tobacco product users did not die significantly earlier than non-users. Conclusion: Tobacco products had a negative impact on periodontal health. Tobacco product users were less educated. However, using tobacco products may not cause premature death.